Комплексный анализ методов оценки гудвила предприятия - Шаша, Е. И. (НТУ "ХПИ", 2010)
У даній статті проведено дослідження з метою систематизації методик комплексного аналізу гудвілу підприємства. Дається аналіз методик і методів оцінки гудвілу з вказівкою їх достоїнств і недоліків.

Research is carried out given article for the purpose of ordering of techniques of the complex analysis goodwill the enterprises. The analysis of techniques and estimation methods goodwill with instructions of their merits and demerits is given.
Keywords: нематериальные активы; деловая репутация; имидж; корпоративная культура; стоимость гудвила; факторы